The Correlations Between Student’s HIV/AIDS Knowledge and Their Attitude toward PLWHA - Linda Prasetyaning Widayanti; Sri Hidayati; Nova Lusiana; Muhamad Ratodi (Journal of Health Science and Prevention, 2018)
HIV/AIDS has become a burden for health in with it sufferers has reached 39 million worldwide. Around 620 thousand PLWHA has been identified all over Indonesia, with Surabaya has been listed among the top five cities with the highest number of HIV / AIDS cases in Indonesia. This study was to determine the correlations between the HIV / AIDS knowledge with the Surabaya college student’s attitude towards PLWHA. This study was observational analytic research with cross-sectional approach. A proportional sampling chose as the research sampling technique, with 250 college students became the respondents. Data were collected from the results of filling out the online questionnaire. A Contingency Phi was used to perform a statistical test. The results indicated only 41.6% of respondents had a good knowledge level about HIV/AIDS, while 77% of the students have already shown a positive attitude towards PLWHA. Furthermore, it is known that there was a relationship between students' knowledge regarding HIV / AIDS and their attitude towards PLWHA with a p-value of 0,000. From these results, it is expected that there will be an HIV/AIDS socialization for college students to increase a more comprehensive knowledge about HIV/AIDS and PLWHA.